2011
DOI: 10.1177/1368430210398014
|View full text |Cite
|
Sign up to set email alerts
|

Social-norms interventions for light and nondrinking students

Abstract: Social-norms approaches to alcohol prevention are based on consistent findings that most students overestimate the prevalence of drinking among their peers. Most interventions have been developed for heavy-drinking students, and the applicability of social-norms approaches among abstaining or light-drinking students has yet to be evaluated. The present research aimed to evaluate the impact of two types of online social-norms interventions developed for abstaining or light-drinking students. Identification with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 46 publications
2
49
0
Order By: Relevance
“…For instance, Stock, Vallentin-Holbech, and Rasmussen (2016) created a program in which pupils first indicate their own substance use and perceived norms through online questionnaires, and subsequently receive corrective information about substance use rates and social norms of their peers. Similarly, Neighbors et al (2011) found that college students in the control condition consumed more alcohol weekly than participants receiving corrective information about peers' alcohol consumption. Social norms interventions adapted specifically for party-drugs may be promising to prevent or decrease party-drug use among college students.…”
Section: Discussionmentioning
confidence: 90%
“…For instance, Stock, Vallentin-Holbech, and Rasmussen (2016) created a program in which pupils first indicate their own substance use and perceived norms through online questionnaires, and subsequently receive corrective information about substance use rates and social norms of their peers. Similarly, Neighbors et al (2011) found that college students in the control condition consumed more alcohol weekly than participants receiving corrective information about peers' alcohol consumption. Social norms interventions adapted specifically for party-drugs may be promising to prevent or decrease party-drug use among college students.…”
Section: Discussionmentioning
confidence: 90%
“…Several potential intervention moderators of alcohol-related outcomes have been examined among college students. These include historical variables, such as age of drinking onset (Mallett, Ray, Turrisi, Belden, Bachrach, & Larimer, 2010) and family history of alcohol abuse (LaBrie, Feres, Kenney, & Lac, 2009), stable individual difference variables, such as gender (Carey, Henson, Carey, & Maisto, 2009; Carey, Carey, Henson, Maisto, & DeMartini, 2011), self-regulation (Carey, Henson, Carey, & Maisto, 2007) and self-determination (Neighbors, Lewis, Bergstrom, & Larimer, 2006), and more malleable variables, such as identification with the typical college student (Neighbors, Jensen, Tidwell, Walter, & Fossos, 2011) and readiness to change (Carey et al, 2007; Tomaka, Palacios, Morales-Monks, & Davis, 2012). Briefly, some interventions have been found to be more effective for more at-risk students including students with an earlier age of drinking onset (Mallett et al, 2010) or with a positive family history of alcohol abuse (LaBrie et al, 2009).…”
Section: Moderators Of Intervention Efficacymentioning
confidence: 99%
“…The utility of electronic screening and brief intervention (eSBI) as a universal prevention strategy has not been well explored. With a few exceptions (e.g., Larimer et al, 2007; Neighbors et al, 2011), there is relatively little evidence that supports feedback-based approaches as a prevention strategy for those who are light or non-drinkers (Elliot, Carey, & Bolles, 2008). Moreover, there is concern that the use of screening and personalized normative feedback as a universal prevention strategy may be irrelevant for non-drinking students or, given some evidence of the potential for iatrogenic effects of these alcohol prevention programs (Werch & Owen, 2002), may even have negative consequences.…”
Section: Introductionmentioning
confidence: 99%